ANALISIS SENTIMEN MENGENAI KESADARAN MASYARAKAT INDONESIA TERHADAP KEAMANAN SIBER DALAM MENGHADAPI KEBOCORAN DATA MENGGUNAKAN ALGORITMA NAÏVE BAYES CLASSIFIER - Dinna Nurfadlillah (LPPM Poltek ST Paul, 2023)
Leakage of personal data is a serious challenge, the adverse effects of incidents of data leakage can result in fines, loss of reputation and public trust that has been harmed. Cyber security plays a role in minimizing the level of risk of cyberattack threats that disrupt the security of all system components such as infrastructure, software, hardware and data. This research was conducted to analyze the sentiments of the Indonesian people towards the queries